2019
DOI: 10.1029/2019wr025080
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Open Science and Data Privacy in the Water Sciences

Abstract: Open science practices such as publishing data and code are transforming water science by enabling synthesis and enhancing reproducibility. However, as research increasingly bridges the physical and social science domains (e.g., socio‐hydrology), there is the potential for well‐meaning researchers to unintentionally violate the privacy and security of individuals or communities by sharing sensitive information. Here we identify the contexts in which privacy violations are most likely to occur, such as working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…Many tweets may relate to dry conditions, on farms and ranches and in other contexts, without using "drought" or "#drought." To hone in on emerging conditions that people may not be hashtagging, i.e., to get past searches for "#drought" or "#drought19," a next step would to explore less visible conversations, possibly starting with search terms such as the production-oriented words that our analysis identified as being distinctive in the #drought17 subset of tweets, or to look for a drought signal in tweets related to planting progress (Zipper 2018). Another possibility would be to filter larger searches based on user profile information, either with comparatively simple filters such as use of the word "ranch," or using natural language processing to develop more refined indicators of agricultural production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many tweets may relate to dry conditions, on farms and ranches and in other contexts, without using "drought" or "#drought." To hone in on emerging conditions that people may not be hashtagging, i.e., to get past searches for "#drought" or "#drought19," a next step would to explore less visible conversations, possibly starting with search terms such as the production-oriented words that our analysis identified as being distinctive in the #drought17 subset of tweets, or to look for a drought signal in tweets related to planting progress (Zipper 2018). Another possibility would be to filter larger searches based on user profile information, either with comparatively simple filters such as use of the word "ranch," or using natural language processing to develop more refined indicators of agricultural production.…”
Section: Discussionmentioning
confidence: 99%
“…Privacy. Ensuring ethical use of individuals' information shared via social media is an evolving consideration for researchers contending with both a move toward more open data and recognition that using publicly shared data in ways not originally intended may be objectionable to Twitter users (Fiesler and Proferes 2018;Ghermandi and Sinclair 2019;Zipper et al 2019). Using hashtagged search terms and filters tended to limit the tweets we collected to a well-defined conversation that was often dominated by media and climate or agricultural professionals.…”
Section: Datamentioning
confidence: 99%
“…For example, ecologists have had few incentives for sharing information because sharing data was not viewed as a valuable scholarly endeavor or as an essential part of science. The research by Zipper et al ( 2019 ) showed that open data and programs are transforming water science by enabling synthesis and enhancing reproducibility, but there might also risks. For example, researchers unintentionally violate the privacy and security of individuals or communities by sharing some sensitive information.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…and potential data misuse (McKenna et al, 2012; Véliz & Grunewald, 2018). Currently, privacy is a sweeping concept, encompassing, in the context of smart water meters, control over personal information (Jamieson, 2009; Solove, 2010; Weaver, 2014; Zipper et al, 2019). Multiple ongoing and unresolved debates regarding the definition of the illusive concept of privacy arise beyond the revealing personal household activities, including ownership of information and, moreover, how this information may be used for discrimination, search, and surveillance (Ząbkowski & Gajowniczek, 2013).…”
Section: Introductionmentioning
confidence: 99%